Rapid eye movement sleep deprivation-induced down-regulation of beta-adrenergic receptors in the rat brainstem and hippocampus - Pedrazzoli, Mario; Benedito, Marco Antonio Campana (Elsevier, 2004)
Rapid eye movement (REM) sleep deprivation induces a cortical down-regulation of beta-adrenergic receptors. Down-regulation of cortical beta-adrenergic receptors is consistently observed after a number of different chronic antidepressant treatments (drugs and electroconvulsive shock). REM sleep deprivation has an antidepressant effect in humans, and in rats, it decreases immobility in the behavioral despair test, an effect also produced by antidepressant treatments. To verify whether REM sleep deprivation also affects hippocampal beta-adrenergic receptors, we carried out the binding of [ 3H]-dihydroalprenolol ([3H]-DHA) to hippocampal membranes from rats deprived of REM sleep for 96 h. We also determined the binding of [3H]-DHA to brainstem membranes, a brain region where noradrenergic nuclei are located. Rats were deprived of REM sleep using a water tank with multiple small platforms. [3H-DHA] saturation conditions (concentrations ranging from 0.15 to 6 nM) were obtained in a crude hippocampus and brainstem membrane preparation. Nonspecific binding was determined using DL-propranolol in hippocampus homogenates. In the brainstem homogenates, nonspecific binding was determined in the presence of DL-propranolol or L-isoproterenol. The results obtained showed statistically significant down-regulation of beta-adrenergic receptors in both the hippocampus and the brainstem after REM sleep deprivation. In the hippocampus, there was also a significant decrease in the dissociation constant (KD). In the brainstem, a significant decrease in KD was observed when DL-propranolol was used to determine nonspecific binding. The down-regulation of beta-adrenergic receptors in the hippocampus and brainstem suggests the involvement of these brain areas in the antidepressant effect of REM sleep deprivation. © 2004 Elsevier Inc. All rights reserved.
Keywords: [ 3H]-Dihydroalprenolol; Beta-adrenoceptors; Binding; Brainstem; Hippocampus; REM sleep deprivation